Pengaruh Kualitas Konten,Electronic Word of Mouth (E-WOM),Brand Awareness Terhadap Niat Beli Produk Meetchin di TiktokShop. - Ameilia Destiara Ahdiat; Dadan Abdul Aziz Mubarok (Universitas Persada Indonesia YAI, 2025)
This study aims to study the impact of Content Quality, Electronic Word of Mouth (e-WOM), Brand Awareness on the intention to purchase Meetchin products on TikTok. For this purpose, data was collected through questionnaires given to TikTok users who had seen or purchased Meetchin products. The methods used in analyzing the data were descriptive statistics and multiple linear regression. The results of the study show that Content Quality, Electronic Word of Mouth, Brand Awareness all have a positive and significant effect on the intention to purchase Meetchin products. Among the three, Content Quality is a less influential factor, followed by e-WOM and Brand Awareness which have an influence on the intention to purchase products. The results of this study provide several recommendations for business actors to improve the Quality of Marketing Content, utilize the influence of e-WOM optimally, and strengthen Brand Awareness to increase consumer purchasing intentions on TikTok.